2007
DOI: 10.1002/chin.200705264
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Radionuclides and Heavy Metals Behaviour in Soils: Implications for Plant Growth

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 2 publications
2
24
0
3
Order By: Relevance
“…Numerous investigations show that the distribution and bioavailability of radionuclides in nature are a function of their chemical fractionation in the soils (e.g. Schultz et al 1998;Rao et al 2008), which depends both upon their physicochemical forms and the soil characteristics (Igwe et al 2005). The long-term differences of the environmental conditions were found to cause redistribution of the radionuclides within the various soil fractions due to changes of the pH, the redox potential, destruction of the organic matter, leaching and ion-exchange (Koch-Steidl and Pröhl 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous investigations show that the distribution and bioavailability of radionuclides in nature are a function of their chemical fractionation in the soils (e.g. Schultz et al 1998;Rao et al 2008), which depends both upon their physicochemical forms and the soil characteristics (Igwe et al 2005). The long-term differences of the environmental conditions were found to cause redistribution of the radionuclides within the various soil fractions due to changes of the pH, the redox potential, destruction of the organic matter, leaching and ion-exchange (Koch-Steidl and Pröhl 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Soil pH is the most widely accepted parameter which exerts a controlling influence on the availability of micro-nutrients and heavy metals in the soil to plants (Sanders, 1982;Igwe et al, 2005). Banjoko and Sobulo, (1994) reported that some Nigerian soils especially in the forest and savannah regions are within a pH range of 5.70 -6.50.…”
Section: Resultsmentioning
confidence: 99%
“…Fine solid particles are also more tractable to migration in soil due to the biological activity of growing plant roots as well as of small organisms and animals living in soil [17]. As a result of the above processes, caesium can migrate carried by soil particles.…”
Section: Resultsmentioning
confidence: 99%